The Canadian Football League: Radically Canadian? - Cantelon, Michael. (University of Ottawa (Canada), 2002)
Sport can be a medium for inculcating national passions and also as an outlet for the transmission of these. Indeed, Canadian professional football has made such claims for its game. The Canadian Football League (CFL) uses marketing slogans like "The Canadian Football League: RADICALLY CANADIAN" and "Our Balls are Bigger" in attempts to attract fans and sell CFL merchandise. The League touts itself as being the only truly Canadian professional sports league and describes its championship game, the Grey Cup, as a national unifying event. In order to answer the general question: How Canadian is the CFL, the study examines the following specific questions: what are the Canadian specificities of the game?, who controls the game?, who plays the game?, how is the game portrayed? Contrary to its rhetoric, the Canadian Football League is a misnomer. The CFL seizes upon the nationalistic passions of the fan base to further its growth while marginalizing the participation of the Canadian player. In fact, the CFL is Canadian in rules only and has, throughout its history, been subject to relentless forces of Americanisation. Using empirical quantitative data for the CFL from 1990--2000 as well as qualitative data throughout the CFL's history, the study demonstrates the diverse ways in which these forces manifest themselves.
Keywords: Canadian Studies.